Comparative study of capillary blood glucose estimation by glucometer and venous plasma glucose estimation in women undergoing the one step DIPSI test (diabetes in pregnancy study group India) for screening and diagnosis of gestational diabetes mellitus - Jadhav, Deepali S.; Wankhede, Uma N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Gestational diabetes mellitus (GDM) is defined as carbohydrate intolerance of variable severity with onset or first recognition during pregnancy. The importance of GDM is that two generations are at risk of developing diabetes in the future. Aim was to study the merits and demerits of capillary blood glucose estimation by glucometer over venous plasma glucose estimation while performing DIPSI test. Methods: It was a hospital based clinical study. 1000 patients were enrolled between 24-28 weeks of gestation and DIPSI test was performed. Patient was instructed to come irrespective of fasting. 75 g glucose dissolved in 200-400 ml of water and patient was asked to drink in 5 minutes. Venous blood was drawn after 2 hours, capillary blood sugar also was measured at the same time by glucometer. Results: Sensitivity of capillary blood sugar (CBS) method in detecting GDM is 100% as compared to venous plasma glucose (VPG) and specificity is 99.46% as compared to VPG. Considering the agreement between two methods for diagnosis of GDM, equal sensitivity of both methods and small number of false positive cases detected by CBS method, due to almost equal specificity (99.46%), CBS method by glucometer can be recommended as an alternative to VPG method as a screening and diagnostic test for GDM. Conclusions: It is appropriate and feasible to offer capillary blood sugar sampling by DIPSI test for screening and diagnosis of GDM. The prevalence of GDM in our study is 8% by capillary blood sugar sampling and 7.5% by venous plasma glucose sampling according to DIPSI test.